Altmetrics: "big data" that map the influence of New Zealand research. Issue 4 (4th June 2018) - Konkiel, Stacy; Guichard, Stephanie
Abstract : Purpose: Altmetrics can offer organizations a unique opportunity to understand the non-traditional scholarly and public influence of their institutions' research. This paper aims to look at bibliometrics and altmetrics for New Zealand research published in 2016 to understand the country's research's reach in social media, mainstream media and public policy, as well as more traditional measures of research impact such as university rankings, citations and publications. Design/methodology/approach: Research insights platform Dimensions was searched for author affiliations and publication dates for papers published in 2016 by New Zealand researchers ( n = 10, 934). The study then used Dimensions to perform citation analysis and Altmetric Explorer to find altmetrics for these journal articles, and to generate visualizations to better interrogate the data set. Findings: Of the 10, 934 papers published in 2016 by New Zealand (2016 NZ) researchers, 5, 413 (49.5 per cent) were mentioned 86, 915 times in one of the 16 sources that Altmetric tracks. Twitter, news outlets and Facebook were among the sources that showed the most engagement with New Zealand 2016 research. Citation analysis tools in Dimensions showed that New Zealand 2016 research had a higher than average Field Citation Ratio (1.51) and Relative Citation Ratio (1.29). Originality/value: This study combines traditional bibliometric analysis with altmetrics to find new insights into the impact of recent New Zealand research. It suggests new means for organizations to demonstrate the value of the research they produce.